(untitled) (International Seven Journal of Multidisciplinary, 2023)
The article discusses the relationship between university multicamping and the concepts of territory and body. The methodology is based on a qualitative approach of descriptive nature with literature review and documentary analysis. In the normative analysis on racial quotas for the university, the parameters that underlie the insertion of social categories were observed. The discussion focuses on multicampia beyond its territorial aspects. It is concluded that the body expresses culture, knowledge, mobility and power, while the university, as a territory, sustains: presence, knowledge, knowledge and cultural exchange, raising a critical look at the multicampi university, as an expression of multiple bodies-territories.